2008
DOI: 10.1016/j.cell.2008.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanistic Insights into STIM1-Mediated Initiation of Store-Operated Calcium Entry

Abstract: Stromal interaction molecule-1 (STIM1) activates store-operated Ca2+ entry (SOCE) in response to diminished luminal Ca2+ levels. Here, we present the atomic structure of the Ca2+-sensing region of STIM1 consisting of the EF-hand and sterile alpha motif (SAM) domains (EF-SAM). The canonical EF-hand is paired with a previously unidentified EF-hand. Together, the EF-hand pair mediates mutually indispensable hydrophobic interactions between the EF-hand and SAM domains. Structurally critical mutations in the canoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
572
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(596 citation statements)
references
References 57 publications
20
572
0
4
Order By: Relevance
“…5E and supplemental Fig. S1F), suggests that a partial destabilization of the EF-SAM domain may ease the transition from the "open" (Ca 2ϩ -bound) to the "closed" (Ca 2ϩ -depleted) state of the molecule (34,36), thereby increasing the rate of oligomerization k 1 (Fig. 6B).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5E and supplemental Fig. S1F), suggests that a partial destabilization of the EF-SAM domain may ease the transition from the "open" (Ca 2ϩ -bound) to the "closed" (Ca 2ϩ -depleted) state of the molecule (34,36), thereby increasing the rate of oligomerization k 1 (Fig. 6B).…”
Section: Discussionmentioning
confidence: 99%
“…Although mutation of a conserved tryptophan adjacent to Asn-131, namely W132R, had little effect on the quaternary structure and oligomerization of the EF SAM domain, mutation of T172R, adjacent to Asn-171, led to persistent EF-SAM aggregation (34). In contrast to earlier work, which showed either reduced STIM1 function upon mutation of the consensus glycosylation site asparagines to glutamines N131Q/N171Q (28) or an unaltered endogenous SOCE (35), we were able to show that prevention of glycosylation does not reduce function per se and that a particular mutant combination, namely N131D/ N171Q (DQ), instead created a strong gain of function mutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent NMR studies revealed a structural basis for this process. In the resting state, a single Ca 2þ ion bound to the canonical EF hand exposes a hydrophobic cleft in STIM1 that interacts with hydrophobic anchor side chains from the SAM domain (Stathopulos et al 2008). In this way, high [Ca 2þ ] ER prevents EF-SAM from engaging in intermolecular interactions, essentially providing a "brake" on spontaneous activation of SOCE.…”
Section: Oligomerization Of Stim Is a Regulatory Switch For Socementioning
confidence: 99%
“…It binds luminal Ca 2+ at its EF hand with an affinity of K d ∼400 µM. When Ca 2+ dissociates from Stim1 during SR Ca 2+ depletion, a conformational unfolding of the EF and the sterile-α-motif permits aggregation of Stim1 molecules into clusters (Stathopulos et al 2008). In Jurkat cells, ER Ca 2+ depletion was associated with local accumulations of Stim1 clusters as "puncta" near the plasma membrane within tens of seconds that coincided with the development of CRAC currents (Wu et al 2006).…”
Section: Store-operated Ca 2+ Entry (Soce) In Skeletal Musclementioning
confidence: 99%